Mesodermal Competence of the Presumptive Ecto-Neuroderm at Various Developmental Stages, in Xenopus laevis (Daudin) - Sri Sudarwati (Institute for Research and Community Services (LPPM) ITB, 1973)
Abstract. A comparative study on the reactive capacity of the presumptive ecto-neuroderm on mesoderm formation with increase of age has been done in Xenopus Laevis. It was proved that before gastrulation, mesoderm induction mainly produces dorsal mesodermal structures. During the gastrulation process the product of differentiation tends to shift from dorsaL to ventral mesodermal structures. The presumptive ecto-neuroderm has has already a competence for mesoderm formation at the early blastula stage and this competence starts to fade out at the horse-shoe-shaped blastopore stage. Ringkasan. Suatu studi perbandingan mengenai kapasitas berreaksi dalam membentuk mesoderm dari presumptive ekto-neuroderm dengan bertambahnya umur, telah dilakukan pada Xenopus laevis. Telah dibuktikan, bahwa sebelum gastrulasi induksi mesoderm terutama menghasilkan struktur-struktur mesoderm dorsal. Selama proses gastrulasi berlangsung, hasil differensiasi cenderung untuk menggeser dari struktur-struktur mesoderm dorsal ke struktur-struktur mesoderm ventral. Presumptif ekto-neuroderm telah mempunyai kompetensi untuk membentuk mesoderm pada stadium blastula muda dan kompetensi tersebut mulai menghilang pada stadium blastoporus berbentuk sepatu kuda.